2020
DOI: 10.1038/s42003-020-01279-4
|View full text |Cite
|
Sign up to set email alerts
|

High pressures increase α-chymotrypsin enzyme activity under perchlorate stress

Abstract: Deep subsurface environments can harbour high concentrations of dissolved ions, yet we know little about how this shapes the conditions for life. We know even less about how the combined effects of high pressure influence the way in which ions constrain the possibilities for life. One such ion is perchlorate, which is found in extreme environments on Earth and pervasively on Mars. We investigated the interactions of high pressure and high perchlorate concentrations on enzymatic activity. We demonstrate that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…We showed that high pressures increase a-chymotrypsin enzyme activity even in the presence of high perchlorate concentrations. 21 The results suggested that high pressures may increase the habitability of environments under perchlorate stress. In another study it has been shown that the driving force for liquid-liquid phase separation and condensate formation of proteins is strongly influenced by the type of Martian salt and its concentration.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We showed that high pressures increase a-chymotrypsin enzyme activity even in the presence of high perchlorate concentrations. 21 The results suggested that high pressures may increase the habitability of environments under perchlorate stress. In another study it has been shown that the driving force for liquid-liquid phase separation and condensate formation of proteins is strongly influenced by the type of Martian salt and its concentration.…”
Section: Discussionmentioning
confidence: 97%
“…One particular ion is perchlorate, ClO 4 À , which is found in extreme environments on Earth and ubiquitously on Mars. [19][20][21] Perchlorates are also known to act as chaotropes, perturbing the structure of water and its hydrogen bonding capacity, 22 and might hence affect biomolecular hydration, structure and function. Perchlorate salts, particularly Mg(ClO 4 ) 2 and Ca(ClO 4 ) 2 , exhibit deep eutectic temperatures allowing for the presence of liquid water at temperatures as low as À70 1C, therefore highlighting the case for their presence in subsurface Martian environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility largely depends on the composition of the reaction medium, temperature, pressure, and pH. The reason behind this multifaceted dependency is the interaction between the enzyme and the surrounding reaction medium as well as the influence of the reaction medium on the interactions of the metabolites 2 , 3 . Thus, including thermodynamic constraints to develop new processes is promising; such constraints help to evaluate that thermodynamically unfeasible routes are excluded.…”
Section: Introductionmentioning
confidence: 99%